Hak Waris Anak Perempuan Menurut Hukum Adat Samin, Desa Klopoduwur, Kabupaten Blora - Kholilah, Iin Nur; Rato, Dominikus; Yasa, I Wayan (Lentera Hukum, 2015)
The samanic society that adheres to Adam's religion that has the principle of honesty, all religions to them equally well. The samin are convinced of a belief in the laws of nature and the law of karma. The people of samin use the title of inheritance instead of inheritance, and in sharing the inheritance of the samin community using the parental system only they do not always know the relationship of blood or the upper generation after the grandparents because they assume that all children are descendants of adam who have rights and obligations same. While the process of dividing the inheritance of the samin community does not distinguish the religion held by its descendants as long as it does not contradict the main points of the teachings of samin, in the division of inheritance as long as the parents are alive to avoid disputes. The author is interested to examine more about the division of inheritance, especially the part of girls in the community of samin, precisely in the village Klopoduwur, Kabupaten Blora. KEYWORDS: Rights of Inheritance, Girls, Samin Customs